PENGALAMAN PASIEN TERPASANG KATETER URIN URETHRAL JENIS INDWELLING DAN INTERMITTEN: QUALITATIVE REVIEW - Sirli Agustiani; Arlina Dewi (Jurnal Surya Muda, 2023)
The use of urinary catheter affect the patient’s life in holistic. There is one review article that explores about experiences of urinary catheter patient’s inserted. But the article only discusses about psychosocial aspect and not discusses patient in holistic. The aim of this research to explore about experiences of urethral catheter patients insertedwith indwelling and intermitten. This research is qualitative review. The researcher searched data from PubMed, SAGE Journals, and Mendeley. The search was restricted to English language articles and limited to last 2001-2020. The main keywords use experience and “urinary catheter*”. There were 23 articles included in the inclusion criteria. Holistically, several experiences were reviewed including physical aspects such as sleep, comfort, pain, physical activity, urinary tract infections, muscle spasm, and bleeding. In psychological aspect, include anxiety, self-adaptation or self-acceptance, self-identity, self-image, self-ideal and self-esteem. In social aspects such as social activity and social interaction. In environmental aspects include size of toilets, toilet cleanliness, material from catheter which affect the environment. In other aspects include patient knowledge, role of health professionals (nurse), and economy crisis. Negative and positive experiences were felt for urethral catheter patients inserted with indwelling and intermitten. Nurses are expected to provide holistic nursing care for patients with urinary catheters.